Kondisi Sosial Ekonomi Pembudidaya Rumput Laut di Desa Apal Kecamatan Liang Kabupaten Banggai Kepulauan - Indra Jaman; Hermon Maurits Karwur; Xaverius Erick Lobja (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2023)
The socioeconomic aspects of seaweed cultivators in Apal Village, Liang District, Banggai Islands Regency are the focus of this study. This study's sub-focus is income, educational background, and seaweed product marketing. The findings state that farmers' incomes are at low and medium levels. Due to financial constraints, high school costs, and a vast distance from secondary schools, seaweed cultivators can only acquire a basic education. Seaweed marketing at the local level. There has been no effort from the government or the community to expand marketing. The impact is that the economic conditions of seaweed cultivators have not improved.